Virus‐like particles for vaccination against cancer. (27th August 2019) - Mohsen, Mona O.; Speiser, Daniel E.; Knuth, Alexander; Bachmann, Martin F.
Abstract: Active immunotherapy of cancer aims to treat the disease by inducing effective cellular and humoral immune responses. Virus‐like particle‐based vaccines have evolved dramatically over the last few decades, greatly reducing morbidity and mortality of several infectious diseases and expectedly preventing cervical cancer caused by human papilloma virus. In contrast to these broad successes of disease prevention, therapeutic cancer vaccines remain to demonstrate clinical benefit. Yet, several preclinical and clinical trials have revealed promising results and are paving the way for medical breakthroughs. This study reviews and discusses the recent preclinical development and clinical trials in this field. This article is categorized under: Biology‐Inspired Nanomaterials > Protein and Virus‐Based Structures Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : Virus‐like particles, a powerful and flexible platform for the development of cancer vaccines.